Child Support, Welfare Dependency, and Poverty - Robins, Philip K. (American Economic Review, 1986)
This paper presents an empirical analysis of the effect of child support enforcement policies on poverty and welfare dependency among female-headed families. A special supplement to the April 1982 Current Population Survey provides the data for the analysis. The results suggest that child support enforcement may represent an effective means for reducing welfare program costs, but is unlikely to have a dramatic effect on reducing either poverty or welfare dependency.